Urodilatin increases renal dopamine uptake: intracellular network involved - Choi, Marcelo Roberto (2011)
Dopamine and urodilatin promote natriuresis and diuresis through a common pathway that involves reversible deactivation of renal Na+, K+-ATPase. We have reported that urodilatin enhances dopamine uptake in outer renal cortex through the natriuretic peptide type A receptor. Moreover, urodilatin enhances dopamine-induced inhibition of Na+, K+-ATPase activity. The objective of the present work was to investigate the intracellular signals involved in urodilatin effects on dopamine uptake in renal cortex of kidney rats. We show that urodilatin-elicited increase in 3H-dopamine was blunted by methylene blue (10 μM), a non-specific guanylate cyclase inhibitor, and by phorbol-12-myristate-13-acetate (1 μM), a particulate guanylate cyclase inhibitor, but not by 1H-[1,2,4]-Oxadiazolo-[4,3-a]-quinoxalin-1-one (10 μM), a specific soluble guanylate cyclase inhibitor; therefore the involvement of particulate guanylate cyclase on urodilatin mediated dopamine uptake was confirmed. Cyclic guanosine monophosphate and proteinkinase G were also implicated in the signaling pathway, since urodilatin effects were mimicked by the analog 125 μM 8-Br-cGMP and blocked by the proteinkinase G-specific inhibitor, KT-5823 (1 μM). In conclusion, urodilatin increases dopamine uptake in renal cortex stimulating natriuretic peptide type A receptor, which signals through particulate guanylate cyclase activation, cyclic guanosine monophosphate generation, and proteinkinase G activation. Dopamine and urodilatin may achieve their effects through a common pathway that involves deactivation of renal Na+, K+-ATPase, reinforcing their natriuretic and diuretic properties.